The relationship between financial leverage and equity returns in Arab stock markets - Shalaby, Sahar (AUC Knowledge Fountain, 2020)
The effect of financial leverage on firm’s performance is one of the most examined and debated issues in finance with an extensive empirical literature that directly or indirectly suggests a role for financial leverage in explaining the cross-sectional dispersion in expected stock returns. This thesis examines the effect of financial leverage on the cross section of equity returns of publicly listed non-financial firms in the Arab Markets. The thesis focused on four main stock exchanges: Amman Stock Exchange, Egyptian Stock Exchange, Kuwait Stock Exchange and Saudi Stock Exchange (Tadawul). The sampling period extended from the first quarter of 2006 to the last quarter of 2019. The total number of eligible firms was 536, 162 firms from Egypt, 123 firms from Jordan, 116 firms from Kuwait, and 135 firms from Saudi Arabia. The Capital Asset Pricing Model, the Fama French 3-factor model and the Fama-French 5-factor model were used to test the relationship between leverage -measured as the book value of total liabilities divided by book the value of assets - and equity returns. The results showed that leverage change and leverage level have no significant relations with stock returns for all countries included in this study.